Guide to modern meals - Ohl, Suzanne Sickler; Duyff, Roberta Larson; Hasler, Doris (New York : Webster Division, 1981)
A senior high textbook focusing on nutrition, meal planning, managing food resources, and the preparation and serving of meals.
First ed. (1964) by D. E. Shank, N. K. Fitch, and P. A. Chapman.
Includes index.
Keywords: Cookery; Nutrition; Food